Designing Resort Wear for Plus Size Women through Kumo Shibori Applications - Yuli Yulianti Ningsih; Naufal Arafah; Wuri Handayani (Journal of Creative Industries and Vocational Innovation, 2026)
Plus-size women continue to face limited fashion options that accommodate body proportions while offering diverse aesthetic expressions. Existing plus-size fashion designs are often dominated by visual slimming approaches, resulting in limited exploration of alternative design perspectives. This study aims to create a resort wear design for plus-size women through the application of Kumo Shibori and crochet techniques as forms of contemporary textile craftsmanship. The study employed an artistic creation method consisting of Observation, Experimentation, Reflection, and Formation stages. Observation focused on the characteristics and needs of plus-size women as well as the exploration of resort wear, Kumo Shibori, and crochet techniques. Experimentation and reflection were conducted to determine the most appropriate design solution before being realized into a wearable garment during the formation stage. The result of this study is a resort wear design that integrates Kumo Shibori and crochet textures to create visual rhythm, textile expression, and handcrafted character. User evaluation conducted with the plus-size model who wore the garment indicated positive responses regarding comfort, mobility, visual appearance, and confidence while wearing the design. The study demonstrates the potential of textile craft techniques as an alternative approach to developing more inclusive, expressive, and representative fashion products for plus-size women.